Analisis Tenaga Kerja Kontrak Dalam Pengoptimalan Kinerja Karyawan PT. XYZ - Salsabila Arinda; Cahyadi, Nur (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This era of development is marked by competition between companies from various sectors. It will also compete with developed countries that have advantages from various aspects ranging from technological aspects and aspects of human resources. An employment agreement is the beginning of an agreement between workers and companies that contains terms of work. Rights and obligations of work, this company is one of the companies that employs some of its employees with a contract system commonly referred to as a Certain Time Work Agreement (PKWT). By knowing the work that is a responsibility and the company employs its workers according to the agreement stipulated in the employment agreement. So this will encourage workers to obey the provisions set by the company. In addition to the workload factor, companies also often use contract labor because contract labor will be able to reduce spending from the labor wage sector